Desenvolvimento de sistema de geolocalização em realidade aumentada para multiplataforma móvel - Santos Júnior, Gesmar de Paula (2015)
Augmented Reality became a popular topic within the field of academic research, especially by providing the user with an overlapping or compounding view of virtual objects and the real world. The use of Augmented Reality in mobile devices is currently growing as a field of research. However, one of the greatest difficulties about developing such application category is the fact that there are a great variety of platforms, programming languages, standards and proprietary SDKs. This work aims to develop a multi-platform outdoor navigation application using Augmented Reality based on geolocation. The application is then developed using PhoneGap, a framework platform for creating mobile applications that uses HTML5 and JavaScript.